Role of Fibroblast Populations in Periodontal Wound Healing and Tissue Remodeling - Smith, Patricio C.; Martínez, Constanza; Martínez, Jorge; McCulloch, Christopher A. (Frontiers in Physiology, 2019)
After injury to periodontal tissues a healing response is initiated that includes a series of sequential phases, which enable wound closure and partial restoration of tissue structure and function. Wound closure in periodontal tissues involves the tightly regulated coordination of resident cells in epithelial and connective tissue compartments. Multiple cell populations in these compartments synergize their metabolic activities to re-establish a mucosal seal that involves the underlying periodontal connective tissues and the tooth surface. The formation of an impermeable seal around the circumference of the tooth is of particular significance in oral health since inappropriate colonization of tooth surfaces by pathogenic biofilms promotes inflammation, which can contribute to periodontal tissue degradation and tooth loss. The reformation of periodontal tissue structures centrally involves fibroblasts, which synthesize and organize the collagen fibers that link alveolar bone and gingiva to the cementum covering the tooth root. The synthesis and remodeling of nascent collagen matrices are of fundamental importance for the re-establishment of a functional periodontium after tissue destruction and are mediated by diverse, multi-functional fibroblast populations that reside within the connective tissues of gingiva and periodontal ligament. Notably, after gingival wounding, a fibroblast sub-type (myofibroblast) arises, which is centrally involved in collagen synthesis and fibrillar remodeling. While myofibroblasts are not usually seen in healthy, mature connective tissues, their formation is increased by wound-healing cytokines and is modulated by the stiffness of the extracellular matrix, which is mechanosensed by resident precursor cells in the gingival connective tissue microenvironment. Here we consider the cellular origins and the factors that control the differentiation and matrix remodeling functions of periodontal fibroblasts. An improved understanding of the regulation and function of periodontal fibroblasts will be critical for the development of new therapies to optimize the restoration of periodontal structure and function after wounding.